VIOLENCE IN SECONDARY SCHOOLS OF ODISHA: PARENTAL PERCEPTION - Lokanath Mıshra (Sakarya University Journal of Education)
This study is aimed to find out the level of parental perceptions of the violent acts, actions parents will take when their children perpetrate violence and how violent acts can be solved in school. 240 students from 24 secondary schools, (10 from each) of Dhenkanal district of odisha were chosen randomly and asked to give the questionnaire to their parents in the survey. The results reveal that parents are aware of violent acts that occur in schools and some of the causes are poor supervision by school authorities , peer influence , exposure to violent media and emotional .inculcating the peace education concept in secondary school curriculum ,emphasising Opportunity for sports and other recreational activities, games, debate, excursions, peace club activities, visitation to schools by parents, community involvement establishment of Guidance and Counselling unit and grievances and readdressal centre are some of the strategies suggested for solving violent behaviour of children in schools.